Hydropower development in the Mekong Region : political, socio-economic and environmental perspectives - Geheb, Kim.; Matthews, Nathanial (Abingdon, Oxon ; New York, N.Y. : Routledge, 2015)
'This book aims to provide a basin wide analysis of the political, socio economic and environmental perspectives of hydropower development in the Mekong Basin. The Mekong Basin is one of the world's most important areas of biodiversity and home to over 70 million people, significant proportions of whom rely directly on these ecosystems for their livelihoods. It is also currently undergoing enormous social, economic, and ecological change of which hydropower development is one of the most significant components. The book includes chapters from China, Thailand, Laos, Cambodia and Vietnam. The book draws from local experts at the region's premier academic institutions to provide a holistic analysis of the shifting socio-political contexts within which hydropower is being framed, legitimised and executed. The book's basin wide approach illuminates how hydropower development, and its benefits and impacts, are linked multilaterally across the basin. The book draws heavily on political ecologies and political economics to examine the economic, social, political and ecological drivers and enablers of hydropower. The research in the book is derived from empirical research conducted from 2012-2013 as part of the CPWF project'--
1. On dams, demons and development : the political intrigues of hydropower development in the Mekong / Nathanial Matthews and Kim Geheb -- 2. Framing a political ecology of Mekong Basin hydropower development / Nathanial Matthews and Kim Geheb -- 3. A political ecology of hydropower development in China / Zha Daojiong -- 4. From Manwan to Nuozhadu : the political ecology of hydropower on China's Lancang River / Xing Lyu -- 5. From Pak Mun to Xayaburi : the backwater and spillover of Thailand's hydropower politics / Jakkrit Sangkhamanee -- 6. The invisible dam : hydropower and its narration in the Lao People's Democratic Republic / Kim Geheb, Niki West and Nathanial Matthews -- 7. Whose risky business? Public-private partnerships, build-operate-transfer and large hydropower dams in the Mekong Region / Carl Middleton, Nathanial Matthews and Naho Mirumachi -- 8. The politics of the Lower Sesan 2 Dam in Cambodia / Kimkong Ham, Samchan Hay and Thea Sok -- 9. Rethinking development narratives on hydropower in Vietnam / Nga Dao and Bui Lien Phuong.
Includes bibliographical references and index.
Also available in print format.
Keywords: Water resources development -- Mekong River Watershed; Water-power -- Mekong River Watershed; Electronic books